KARAKTERISTIK HABITAT GAJAH SUMATERA (Elephasmaximus sumatranus Temminck.) DI TAMAN NASIONAL TESSO NILO DAN SEKITARNYA, PROVINSI RIAU - Bucika Parta Gezali; Defri Yoza; Nurul Qomar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Elephants are large mammals that live in Indonesia especially in Sumatra Island usually called Sumatran Elephants. Population of Sumatran Elephants continues to decrease because the habitat in natural forests is shrinking. One of causes about decline the population because land contriction. Damage and descent in area Sumatran Elephant habitat will have an impact on the availability of elephant feed. This reason can result in the transfer of roaming areas and shifting the elephant's habitat. This study aims to determine the characteristics of elephant habitat in the Tesso Nilo National Park and its surroundings. The study was used the method purposive sampling by determined the habitat characteristics of Sumatran elephants. Characteristics of elephant habitat in TNTN and surrounding areas are four types of vegetation, namely canopy closure in natural forests 31.25-68.59%, shrubs 0%, acacia stands 35.77-58.83%, oil palm plantations 50.98-64.76%. Availability of feed plants in in natural forests 22.22-62.96%, shrubs 8.11-94.44%, acacia stands 42.11-80.77%, oil palm plantations 0-90.79% and the availability of body scrub trees was only found in natural forests, that is 8 trees while other locations are not found. Characteristics of elephant habitatin natural forests, shrubs, acacia stands, oil palm plantations including lowland and has a flat topography. The distance from natural forest to scrub is 4-291 m, acacia stands 4.750-5.270 m, oil palm plantations2.580-2.900 m. The distance to water sources from natural forests is 3-218 m, bushes 4-198 m, acacia stands 348-525 m, oil palm plantations 535-811 m. Keywords:Elephant, location, characteristic, habitat